(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article analyzes new innovations in the field of education in Uzbekistan. In addition, the article discusses the importance of women’s education in today’s information society and the new transition to digital learning - Hemis. Thanks to these developments, government education is becoming more advanced and efficient.